Audit Implementasi Sistem Informasi Toko Thrift Vansesco Boutique Menggunakan COBIT 4.1 - Lusya Yulfaturrahmi; Vita Rahayu (Jurnal Bangkit Indonesia, 2025)
Technology is certainly beneficial for business and education. It makes all human activities or activities easier in information technology. However, it needs to be balanced with an information system audit to prevent losses at Thrift Vansesco Boutique. Thrift Vansesco Boutique is a business engaged in the clothing sector. Thrift Vansesco Boutique is located at Jl. Teladan Km, 2 No. 02 Tanjungpinang Barat, Riau Islands. The study aims to determine how well the web information system functions in the business transaction process at Thrift Vansesco Boutique, make suggestions and improvements to governance after finding an imbalance between the governance used and determine the level of maturity of the Thrift Vansesco Boutique website implementation as expected in the implemented structure. In this case study, the COBIT 4.1 method is used as the framework, and data collection is carried out by interviewing the resource persons, namely the owner and admin of the store. The data analysis process consists of determining the domain, controlling, determining indicators and maturity levels.